Financial Vulnerability of Dairy Farms Challenged by Johne's Disease to Changes in Farm Payment Support - Shrestha, Shailesh; Vosough Ahmadi, Bouda; Barratt, Alyson S.; Thomson, Steven G.; Stott, Alistair W. (Frontiers in Veterinary Science, 2018)
Johne’s disease is an endemic contagious bacterial infection of ruminants prevalent in the UK and elsewhere. It can lower financial returns on infected farms by reducing farm productivity through output losses and control expenditures. A farm-level analysis of the disease was conducted taking account of farm variability and different disease prevalence levels. The aim was to assess the financial impacts of a livestock disease on farms and determine financial vulnerability of the farms if farm support payments are removed under future policy reforms. A farm-level optimisation model, ScotFarm, was used on 50 Scottish dairy farms taken from the Farm Business Survey to determine the impacts of the disease. A counterfactual comparison of the five alternative ‘disease’ scenarios with a ‘no-disease’ baseline scenario was carried out to evaluate economic impact of the disease. The extent of a farm’s reliance on direct support payments was considered to be an indicator of financial vulnerability of the farms. Under this definition, farms were grouped into three financial vulnerability risk categories; ‘low risk’, ‘medium risk’ and ‘high risk’ farms. Results show that farms are estimated to incur a loss up to 51% of average on their net profit under different disease prevalence levels. Farms in the ‘low risk’ and ‘medium risk’ categories were estimated to have a lower financial impact of the disease which along with their lower reliance on farm direct support payments indicate these farms to be more resilient to the disease under future changes in farm payment support. On the contrary, 18% of the farms were grouped in the ‘high risk’ category which relies substantially on farm direct support payment to stay profitable. These farms are projected to have a higher economic impact of the disease which makes these farms more vulnerable if changes are made in farm support payments under future agricultural policy reforms.